ANGKA FIB-4 DAN HIGHLY ACTIVE ANTI RETROVIRAL THERAPY DI ANTARA PASIEN PENGIDAP INFEKSI HIV - Liliana A; Noormartany Noormartany; Sugianli AK (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Liver disease in patients with HIV infection can be caused by hepatotropical virus co infection or as a side effect of antiretroviraltherapy. The cause of HAART effects on liver fibrosis among patients with HIV infection is not yet known. The monitoring of the incidenceof liver fibrosis can be done with non-invasive markers, such as FIB 4 score. FIB-4 score is calculated by the formula: Age x AST/totalplatelet x √ALT. This is carried out to know the comparison of the FIB-4 score in HIV patients before and after first-line HAART therapy,with or without HCV coinfection. This study was a comparative analysis of retrospective data of patients at the Outpatient Teratai Clinic,Dr. Hasan Sadikin Hospital, from 2003 through 2013. The research subjects consisted of 64 patients with HIV infection who receivedfirst-line HAART therapy for more than 12 months. Statistical analysis was performed by Wilcoxon test for two paired samples. Themedian scores of FIB-4 from HIV infection patients with or without HCV co infection before and after the administration of first-lineHAART therapy were 0.854 and 0.906 (p=0.837). The HCV co infected patients had median scores of FIB-4 before and after treatment at0.854 and 0.899 (p=0.204). Those without HCV co infection had median scores of FIB-4 before and after treatment at 2.726 and 0.912(p=0.013).Treatment with first-line HAART did not lead to a change in the FIB-4 score. Those who were co infected with HCV showed nodifferences in the FIB-4 scores before and after treatment with first-line HAART.